4G Network Development as OpenBTS Using Open5GS with Universal Software Radio Peripheral (USRP) B210 Device - Meilisya Eka Saputri; Sopian Soim; Aryanti Aryanti (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
There are a small number of villages across Indonesia that have access to telecommunications. Operators find it less profitable to build conventional telecommunications infrastructure in rural areas. 4G networks need to be developed in various ways, but the development has not yet achieved the quality of service that people need. This article evaluates the performance of developing an OpenBTS4G Network using 5GS with the Universal Software Radio Peripheral (USRP) B210 device to make the network an economical communication solution for villagers. The system can be mobilized and set up whenever the cellular infrastructure is reactivated. After our configuration, the 4G network was detected on several cellular phones, but the transmitted network only covers 5m area, because the power used has not been able to cover a wider area. The development of this network is a solution in building a Network so that it will help people who live in blankspot areas. This research also aims to show that the Universal Software Radio Peripheral (USRP) B210 can be used to provide and 4G Network.